(untitled) (Research, Society and Development, 2021)
With the covid-19 pandemic, basic and higher education institutions were forced to continue their educational processes through remote learning. Therefore, new challenges emerged both in relation to the use of technologies and pedagogical aspects. Thus, the objective of this work was to observe the feasibility of using active methodologies with synchronous and asynchronous activities in the context of remote teaching in a Biological Sciences Graduation Course. The work involved 11 students enrolled in the disciplines of Ecology and Regional Ecology at the Faculty of Education of Crateús-State University of Ceará (FAEC-UECE) during the semester 2020.1. On that occasion, the students elaborated hypotheses for the questions suggested by the professor and elaborated arguments that corroborated or not with their proposals. For data collection, a questionnaire was applied through Google forms. According to the data, the students study study if the method was used positively to provide the best information in the contents of the disciplines and to build the vision critique of the local reality. In this way, we were able to gain that the experience lived with the use of Active Methodologies in remote education in the subjects of Ecology and Regional Ecology provided an adequate environment for the active production of students and consequent learning.